Tradução, adaptação para língua portuguesa e validação da Escala de Experiências Discriminatórias dos Negros - EEDN - Bezerra, Claudia Mara de Oliveira (2014)
The present study holds as a goal presenting the process of translation and validation to the Brazilian context the reduced version of the Index Race-Related Stress (IRRS) Scale of Discriminatory Experiences towards African-descent (SDEA), which measures the stressors motivated by racism related to the experience of the African-descent people. The stress is a phenomenon resulting from continuous evaluations of stimulus perceived through the pressures of the environment, psychological pressures and biological misfits which come from the activation of adaptive resources in front of the stressing situation. It is noticed that the racism and discrimination give a favorable context to the creation and maintenance of the stressing events, in other words, the discriminatory experiences bring cumulative negative situations which interfere in the adaptation of the individual. The original scale original, Index Race-Related Stress (IRRS), comprehends three factors related to the Cultural Racism (ten items), Institutional Racism (six items) and Individual Racism (six items) with items that talk about the statements related to the experiences of the subjects towards the racism. The initial part of the validation was the translation process, reverse translation and semantic analysis, attested by five judges. Initially it was realized the first pre-test with fifteen graduation students, checking the comprehension and clearance of the items. Students from different graduation courses from public and private universities from the state of Sergipe participated in the study, from both genders and ages varying from 17 to 35 years old. In order to distinguish the European-descent and African-descent students, it was used an indicator of social approximation of social groups taking into consideration the color of the skin, which presented eight points, because the skin color appears as the main criterion to the process of validation of the Scale of Discriminatory Experiences towards African-descent (SDEA). In the end of the collecting process, the study counted on 220 graduation students who categorized themselves in the social group of the African-descents and 300 who categorized themselves as inserted in the social group of the European-descents. Afterwards, exploratory factorial analysis with promax rotation procedures were performed, just like analysis of reliability and commonalities, besides the item-scale correlation, the statistical analysis of the socio-demographic variables and the validity concurrent to the scale of perceived stress (PSS-10). In the results, two factors with Alfa of Cronbach between 0,90 were found and factorial charges varying from 0,448 to 0,771to the total score, these results did not correspond to the original structure due to the transcultural aspect. The SDEA validated version resulted in 22 items, revealing itself as bifactorial and with one total factor, being this one the most adequate theoretical and empirical structure. The factors were denominated as: Factor I- Collective Experiences of Racial Discrimination and Factor II- Individual Experiences of Racial Discrimination which reflect on discriminatory experiences in collective and individual contexts. At last, it was performed the concurrent validity between the SDEA and PSS-10, the results demonstrated positive and meaningful correlation to both Factors, although the Factor I has presented the significance a little above p < 0,05. On the other hand, the total score resulted in positive and meaningful correlation as it was expected. The values of SDEA versus PSS-10 revealed bigger punctuations being proportional to the greatest scores of the scale of perceived stress. In resume, it is suggested that the final version of the SDEA translated to Portuguese and composed by 22 items is adequate to the context of the Brazilian researches.